IMPLEMENTASI PERATURAN MENTERI SOSIAL NOMOR 1 TAHUN 2018 TENTANG PROGRAM KELUARGA HARAPAN DALAM MENANGGULANGI KEMISKINAN DI DESA TANETE KECAMATAN TOMPOBULU KABUPATEN - Nur Alisa; Imam Suyitno; Bakhtiar Bakhtiar; Najamuddin Najamuddin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2024)
he aim of this research is to understand (1) How the Family Hope Program plays a role in overcoming poverty in Tanete Village, Tompobulu District, Gowa Regency. (2) Effectiveness of the Family Hope Program in Tanete Village, Tompobulu District, Gowa Regency. (3) Factors that hinder the implementation of the Family Hope Program in dealing with poverty in Tanete Village, Tompobulu District, Gowa Regency. This research used a qualitative approach, with informants consisting of PKH Facilitators, Tanete Village Welfare Head, Posyandu Cadres, and Beneficiary Families (KPM) of the Family Hope Program (PKH). Data was obtained from primary and secondary sources through observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results show that: (1) The implementation of PKH in Tanete Village has been coordinated from the start, but has not been effective in reducing poverty, only helping to reduce the expenditure burden on poor families. (2) The effectiveness of PKH in Tanete Village is considered to be in accordance with the rules for determining prospective participants, even though there are differences in the amount of assistance at each disbursement stage due to discrepancies in the disbursement schedule. (3) Inhibiting factors include the Integrated Social Welfare Data (DTKS) not being updated, data discrepancies with reality, limited PKH assistance quotas, and a lack of PKH assistants.